Clinical outcomes and prognostic determinants of endodontic–periodontal lesions: A retrospective study - Swapna Munaga (Bioinformation, 2026)
Endodontic–periodontal lesions are complex conditions in which both endodontic and periodontal disease coexist, potentially compromising tooth prognosis if not diagnosed and managed properly. Hence, this retrospective study evaluated 100 patients treated between 2020 and 2025 at a tertiary dental care institution to determine treatment success, survival and failure rates, along with prognostic factors. Clinical records and radiographs were analyzed for age, gender, smoking, diabetes, lesion type, pocket depth, mobility, furcation involvement, bone loss, treatment sequence and coronal restoration quality, with outcomes classified after at least 12 months of follow-up. Healing was observed in 61% of cases, survival in 24% and failure in 15%, while better outcomes were associated with mild periodontal destruction, absence of furcation involvement, adequate coronal restoration and early endodontic intervention. Thus, we show that prognosis in endodontic–periodontal lesions is driven mainly by periodontal severity, systemic health and treatment quality, underscoring the value of early diagnosis and multidisciplinary planning.